Pelatihan Keterampilan Digitalisasi Proses Pembelajaran untuk Meningkatkan Kompetensi Guru SMA - Fitrianingrum, Aufa Maulida; Kurniahtunnisa, Kurniahtunnisa; Agustina, Tika Putri (Ilin Institute, 2024)
The purpose of this community service is to enhance the competency of teachers at SMA Negeri 1 Eris in creating digitalized teaching materials. The community service implementation consists of three stages: preparation, training, and evaluation. The evaluation of the activities uses a questionnaire that is analyzed descriptively and quantitatively. The results of this service indicated an improvement in the competencies of SMA Negeri 1 Eris teachers in creating digitalized teaching materials using Google Workspace for Education, Canva, Mentimeter, and Quizizz. The implementation of the activities received positive feedback from participants, as evidenced by their enthusiasm and active participation throughout the program. The evaluation results of the activities show that the level of satisfaction and improvement in teacher competencies after the training is in the very good category. Teachers at SMA Negeri 1 Eris are very interested in developing digitalized teaching materials.